Recovery lithium and potassium from lepidolite via potash calcination-leaching process. (1st January 2021) - Kuai, Yuqing; Yao, Wengui; Ma, Hongwen; Liu, Meitang; Gao, Yuan; Guo, Ruoyu
Highlights: The mechanism of lepidolite-potash calcination process was studied. The calcination could generate acid-soluble KAlSiO4 and water-soluble silicates. Over 95% of soluble lithium and potassium could be easily extracted from generated silicates. The solid residue KAlSiO4 could be easily recovered. Abstract: A new comprehensive way to extract lithium and potassium from lepidolite through calcination process with the additive of K2 CO3 has been proposed. By using flowing water vapor, the lepidolite concentrate mixed with 58.5% of K2 CO3 could generate acid-soluble potassium aluminum silicate (KAlSiO4 ) and water-soluble lithium/potassium silicate (Li2 SiO3 /K2 SiO3 ) at 850 °C for 2 h. Additionally, 80% of fluorine could be removed. The reaction feasibility between lepidolite ore and K2 CO3 was firstly evaluated through thermodynamic calculation. The decomposition mechanism was explored through XRD and TG-DSC analysis. The experimental results reveal that the decomposition of lepidolite undergoes following phase transformation: trilithionite phase → lepidolite phase → KAlSi2 O6 → KAlSiO4 . As the desilication process proceeds, silicon is given off and forms lithium/potassium silicate. Through a water leaching process, soluble Li2 SiO3 /K2 SiO3 could be separated from KAlSiO4 . The extraction efficiency of Li and K could severally reach 95.52% and 95.70% from soluble silicates through water leaching process, under the optimum conditions. Then the residue KAlSiO4 could be easily recovered by acid solution. This new technique for processing lepidolite could make most of all of its components, as well as being environmentally friendly.